Towns and cities carbon emission: case of Kano metropolis Nigeria - Abdullahi, Hashim; Asmawi, M. Zainora; Abdul Aziz, Abdul Razak (Science China Press, 2023)
The study involved fieldwork conducted in the Kano metropolitan area (KNMA), with four hundred structured questionnaires divided into; low-carbon society residents’ perceptions, and the effects of rapid population growth. Geographical Information System (GIS) was employed for the locational map productions and descriptive statistics were used for data analysis and presentation. The results show that (a) Indoor carbon emission is affected by household sizes, the number of people, ages, gender, level of education, and incomes of the dwellers, while (b) Outdoor carbon emission is affected by transportation networks, industrial activities, types of land uses, density types, and income levels of the residence of the area. There is therefore a strong need to embark on the utilization of architectural green building technologies, concepts of clean energy implementation and promotions, local but environmentally friendly building materials utilizations, and effective development control implementations are highly essential.